If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 = 7(3 + x) 49 = (3 * 7 + x * 7) 49 = (21 + 7x) Solving 49 = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 49 + -7x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 49 + -7x = 21 + 0 49 + -7x = 21 Add '-49' to each side of the equation. 49 + -49 + -7x = 21 + -49 Combine like terms: 49 + -49 = 0 0 + -7x = 21 + -49 -7x = 21 + -49 Combine like terms: 21 + -49 = -28 -7x = -28 Divide each side by '-7'. x = 4 Simplifying x = 4
| 5x-3x^2=-8 | | 21-9r=66 | | 5.1(4+2x)-6.4=14 | | 2x+4p=8 | | (x/14)-(1/4)=((x+3)/7) | | 3/5x+1=25 | | 5y-6+y+38=7y+40-5y | | ((x+2/x-2))*(2x+5) | | 6(2+1)=x | | y-4(3-4y)=2-0 | | 8x-10-3x+9=1 | | t+10-3t=-11 | | (x/14)-(1/4)=(x+3/7) | | -4x-13x=68 | | 3(13/3)-4=31 | | 3(5/3)-4=31 | | 9(6+k)= | | 3(5/3) | | (X+7)(x-9)= | | 3(12/3) | | 1/2(10x-9)=3 | | 3(2/3) | | 4r+6=38 | | 5/2-x/4=17/8 | | -2+13=4b-3-3b | | z^2+11z=12 | | 4(x-1)=-6(x+2)+48 | | m^2+12m-68=-4 | | 4(2x-3)=202 | | x/3-12=0.5 | | 0.3(x+100)+0.1x=34 | | 2(3x:6)-5(4+4x)=52 |